i need help on how to solve this problem

  • i need help on how to solve this problem

    Posted by LAURA  on June 20, 2021 at 3:28 pm

    simultaneous equations someone please help me – Andre has more money than Bob. If Andre gave Bob $20, they would have the same amount. While if Bob gave Andre $22, Andre would then have twice as much as Bob. How much does each one actually have?

    avataravatar
    Nwamaka Okafor replied 1 year, 1 month ago 4 Members · 5 Replies
  • 5 Replies
  • Wuche Innocent

    Member
    July 14, 2022 at 12:51 pm

    X+y=20….(1)

    2x+y=22…(2)

    Using elimination method, subtract eqn(1) from (2).

    2x-x +y-y=22-20

    X=2.

    Solving for y in eqn(1); substitute the value of X=2

    2+y=20

    Y=20-2

    Y=18

    avataravataravatar
  • 641489f496fce bpthumb

    D2

    Member
    December 20, 2022 at 8:57 am

    hey that cant be right

    because according to your definition they both have less than 20 dolllars

  • 641489f496fce bpthumb

    D2

    Member
    December 20, 2022 at 9:02 am

    a – 20 = b + 20… 1

    2(b – 22) = a + 22… 2

    We can juggle those around for

    a = b +40 and

    2b – 44 = a + 22 so 2b – 66 = a

    The equations are now:

    a = b + 40 and

    a = 2b – 66

    ELIMINATION METHOD:

    b + 40 = 2b – 66 so 40 = b – 66 making b = 106.

    Plug b = 106 into new equations 1 and 2 for:

    a = 106 + 40 (new equation 1) and

    a = 212 – 66 (new equation 2)

    This gives a = 146 and b = 106

    avataravatar
  • 641489f496fce bpthumb

    D2

    Member
    December 20, 2022 at 9:04 am

    For the purpose of the equations, I’ll call Andre and Bob a and b respectively.

    a – 20 = b + 20 (equation 1)

    2(b – 22) = a + 22 (equation 2)

    We can juggle those around for

    a = b +40 (equation 1r (re-arranged)) and

    2b – 44 = a + 22 so 2b – 66 = a (equation 2r (rearranged))

    The equations are now:

    a = b + 40 (new equation 1) and

    a = 2b – 66 (new equation 2)

    Substitute from new equation 1 to new equation 2:

    b + 40 = 2b – 66 so 40 = b – 66 making b = 106.

    Plug b = 106 into new equations 1 and 2 for:

    a = 106 + 40 (new equation 1) and

    a = 212 – 66 (new equation 2)

    This gives a = 146 and b = 106

    avataravataravataravatar
  • profile avatar buddyboss 50

    Nwamaka Okafor

    Member
    January 16, 2023 at 8:46 am

    Please, how can I unlock the lessons here? Thanks

error: Alert: Content selection is disabled!!